Environmental Nontuberculous Mycobacteria in the Hawaiian Islands. - Jennifer R Honda; Nabeeh A Hasan; Rebecca M Davidson; Myra D Williams; L Elaine Epperson; Paul R Reynolds; Terry Smith; Elena Iakhiaeva; Matthew J Bankowski; Richard J Wallace; Edward D Chan; Joseph O Falkinham; et al. (Public Library of Science (PLoS), 2016)
Lung disease caused by nontuberculous mycobacteria (NTM) is an emerging infectious disease of global significance. Epidemiologic studies have shown the Hawaiian Islands have the highest prevalence of NTM lung infections in the United States. However, potential environmental reservoirs and species diversity have not been characterized. In this cross-sectional study, we describe molecular and phylogenetic comparisons of NTM isolated from 172 household plumbing biofilms and soil samples from 62 non-patient households and 15 respiratory specimens. Although non-uniform geographic sampling and availability of patient information were limitations, Mycobacterium chimaera was found to be the dominant species in both environmental and respiratory specimens. In contrast to previous studies from the continental U.S., no Mycobacterium avium was identified. Mycobacterium intracellulare was found only in respiratory specimens and a soil sample. We conclude that Hawai'i's household water sources contain a unique composition of Mycobacterium avium complex (MAC), increasing our appreciation of NTM organisms of pulmonary importance in tropical environments.